2020
DOI: 10.1039/d0na00164c
|View full text |Cite
|
Sign up to set email alerts
|

Au nano-urchins enabled localized surface plasmon resonance sensing of beta amyloid fibrillation

Abstract: LSPR sensing of structural changes of beta amyloid fibrillation at the nano-molar concentration level using Au nano-urchins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…On the other hand, the progress in the fibrillation process of Aβ 1–42 at nM concentrations was sensed according to the reduction of LSPR peak intensity of gold nano-urchins (AuNUs). With this method, the LSPR of AuNUs at 650 nm gradually decreased with time ( Figure 8 B) an effect that was also evident at various fibrillation stages of Aβ 1–42 ( Figure 8 B) [ 122 ]. In addition, Aβ fibrillation at nM concentrations using AuNSps and AuNUs revealed that AuNSps did not show significant changes in optical absorption compared to AuNUs at various fibrillation stages ( Figure 8 B), thus limiting its capacity for sensing low concentrations in the fibrillation process.…”
Section: Plasmonic Biosensors For In Vitro Optical Detection Of Admentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, the progress in the fibrillation process of Aβ 1–42 at nM concentrations was sensed according to the reduction of LSPR peak intensity of gold nano-urchins (AuNUs). With this method, the LSPR of AuNUs at 650 nm gradually decreased with time ( Figure 8 B) an effect that was also evident at various fibrillation stages of Aβ 1–42 ( Figure 8 B) [ 122 ]. In addition, Aβ fibrillation at nM concentrations using AuNSps and AuNUs revealed that AuNSps did not show significant changes in optical absorption compared to AuNUs at various fibrillation stages ( Figure 8 B), thus limiting its capacity for sensing low concentrations in the fibrillation process.…”
Section: Plasmonic Biosensors For In Vitro Optical Detection Of Admentioning
confidence: 98%
“…LSPR sensing of various fibrillation stages of Aβ 1-42 and comparison between LSPR sensing of Aβ fibrillation at nM range, using AuNUs (blue) and AuNSps (red). The three figures were obtained from ref [122]. published by The Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…The same authors provide also a very good review on the strain transfer theory of fiber optics [26]. In several studies, the Surface Plasmon Resonance (SPR) technique was utilized to improve the sensitivity and durability of the sensors [27][28][29][30][31][32][33]. The purpose of enhancing the sensitivity and durability of the sensor is to enhance the key parameters of the system, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Among all techniques and methods, optical-based techniques have advantages in fast and direct monitoring of targets, simple system design, high sensitivity, real-time measurement, a small volume of samples, and system portability [30][31][32][33][34][35]. To overcome the aforementioned limitations, optical sensor-based methods such as optical nanosensors and surface plasmon resonance (SPR) were developed in the last decade [3,17,[35][36][37][38][39][40]. Fiber optic-based measurement techniques allow high accuracy, fast response, low cost, simplicity, portability, specificity, and higher sensitivity [41,42].…”
Section: Introductionmentioning
confidence: 99%